Insect-resistant biotech crops and their impacts on beneficial arthropods - Gatehouse, A. M. R. (The Royal Society, 2011)
With a projected population of 10 billion by 2050, an immediate priority for agriculture is to achieve increased crop yields in a sustainable and cost-effective way. The concept of using a transgenic approach was realized in the mid-1990s with the commercial introduction of genetically modified (GM) crops. By 2010, the global value of the seed alone was US $11.2 billion, with commercial biotech maize, soya bean grain and cotton valued at approximately US $150 billion. In recent years, it has become evident that insect-resistant crops expressing δ-endotoxin genes from Bacillus thuringiensis have made a significant beneficial impact on global agriculture, not least in terms of pest reduction and improved quality. However, because of the potential for pest populations to evolve resistance, and owing to lack of effective control of homopteran pests, alternative strategies are being developed. Some of these are based on Bacillus spp. or other insect pathogens, while others are based on the use of plant- and animal-derived genes. However, if such approaches are to play a useful role in crop protection, it is desirable that they do not have a negative impact on beneficial organisms at higher trophic levels thus affecting the functioning of the agro-ecosystem. This widely held concern over the ecological impacts of GM crops has led to the extensive examination of the potential effects of a range of transgene proteins on non-target and beneficial insects. The findings to date with respect to both commercial and experimental GM crops expressing anti-insect genes are discussed here, with particular emphasis on insect predators and parasitoids.